Dr. Fatma Saada Emin Kaatcilar, One of the First Female Physicians of the Turkish Republic (1898-1982) - YILDIRIM, NURAN; YILDIRIM N. (My University, 2023)
In the early 20th century, since Istanbul University (Darulfunun) Faculty of Medicine did not accept female students, girls who wanted to study medicine began to go to Europe and America. First, Fatma SaadaEmin and Suad Mahmud Hanim from Izmir were sent to the SwitzerlandGeneva Medical Faculty, with their allocations and education expenses paid by the Aydin Province Special Administration (1915). The following year, the Ministry of Education sent Safiye Ali from Istanbul to the Faculty of Medicine of the University of Wurtzburg in Germany (1916). While they were continuing their education, as a result of the struggle initiated by the girls who wanted to become doctors in Istanbul, Istanbul University\"s Faculty of Medicine started to accept female students (1922). The province of Aydin sent Fatma Saada Emin 20 Ottoman liras every month and also paid 400 Francs as an annual education fee. The First World War ended in 1918, but due to the economic depression caused by the war conditions, this amount could not meet the young student\"s allocation needs. Their allocations were cut off when the Greeks occupied Izmir while the War of Independence was continuing. Fatma Saada Emin and Suad Mahmud Hanim, whose education was in jeopardy, applied to the Ottoman Consulate General in Geneva and expressed their grievances, and their situation was reported to Istanbul. The education expenses of both of them began to be paid from the Istanbul Province budget after 1921. Fatma Saada Emin completed her education, which was prolonged due to war conditions, in 1927 and received a diploma. After completing her specialization in internal medicine, she returned to Izmir. When she received her diploma equivalence certificate, she was appointed to the internal medicine clinic of Izmir Memleket Hospital (1930). Later, she opened a practice in Karsiyaka and started practicing freelance medicine (1932). In the 1943 general elections, she was elected as a member of parliament for the first term and entered the Turkish Grand National Assembly representing Manisa. (1943-1946). When her term as a member of parliament ended, she returned to Izmir and continued to work as a physician in Karsiyaka. Dr. Fatma Saada Emin Kaatcilar did not marry and devoted her life to her patients. She has an important place in the history of Turkish Medicine and women\"s studies, as she is one of the first two female students to go to Europe to study medicine, and in our political history, as the second elected female physician MP. However, no detailed research has been carried out on her so far. In this article, by sharing the information we have compiled from the sources we have access to, Dr. Fatma Saada Emin Kaatcilar is introduced, who served as a health guard for the people of Karsiyaka until her death, and who had the courage to go to a foreign country alone in the turbulent years of WW1, taking on a challenging education such as medicine, in a time when it was not tolerated for girls to even study.
Keywords: Sosyal ve Beşeri Bilimler; Tarih; Social Sciences and Humanities; History; TARİH; Sanat ve Beşeri Bilimler; Sanat ve Beşeri Bilimler (AHCI); HISTORY; ARTS & HUMANITIES; Arts & Humanities (AHCI); Koruma; Sanat ve Beşeri Bilimler (çeşitli); Genel Sanat ve Beşeri Bilimler; Sosyal Bilimler ve Beşeri Bilimler; Conservation; Arts and Humanities (miscellaneous); General Arts and Humanities; Social Sciences & Humanities